Challenge of culture in Africa : from restoration to integration - Fonlon, Bernard Nsokika, 1924-1986 (Langaa RPCIG ; Distributed in N. America by Michigan State University Press, 2010)
This book was first published as a two-part essay in 1965 and 1967 in ABBIA Cameroon Cultural Review under the title Idea of Culture. Its main argument is that indigenous Africans cultures must be the foundation on which the modern African cultural structure should be raised; the soil into which the new seed should be sown; the stem into which the new scion should be grafted; the sap that should enliven the entire organism. This culture, the object of imperialist mockery and rejected, needs rehabilitation. However, such rehabilitation of African culture cannot be a mere archaeological enterprise. It will not answer to dig up the past and live it as it was. Not only is African culture not without its imperfections, times change and African culture must adapt itself, at every turn, to the changing times. In restoring African culture, it is imperative to steer clear of two extremes: on the one hand, the imperialist arrogance which declared everything African as only fit for the scrap-heap and the dust-bin, and, on the other hand, the overly enthusiastic and rather naive tendency to laud every aspect of African culture as if it were the quintessence of human achievement.